Improving NICU staff decision-making with parents in medical rounds: a pilot study of reflective group dialogue intervention - Ahlqvist-Björkroth, Sari; Thernström Blomqvist, Ylva; Nyberg, Jenni; Normann, Erik; Axelin, Anna (Frontiers in Pediatrics, 2023)
Introduction: The communication skills of healthcare professionals play a crucial role in successful shared decision-making with parents in neonatal intensive care. Improving communication skills can be achieved through practice and reflection on personal experiences after authentic interaction events with parents. The process of reflection typically involves three phases: description, reflection, and critical reflection. In this study, our aim was to explore the acceptability of the Reflective Group Dialogue intervention and its effectiveness in supporting the reflective process. Methods: This qualitative pilot study was conducted in the neonatal intensive care unit at Uppsala University Children's Hospital, Sweden. The sample consisted of nine medical rounds with seven families, five neonatologists, seven registered nurses, and five assistant nurses. Purposive sampling was used to collect the data. The intervention comprised four elements: 1) before the intervention, a recorded presentation on shared decision-making was given to the entire unit staff, 2) an observation of a normal medical round discussion with parents, 3) an interview with parents about their experience after the same round, and 4) a reflective discussion with the participating health care professionals after the round. The parent interviews and reflective discussions were audio-recorded and transcribed verbatim. They were analyzed using thematic analysis as a theoretical strategy. Results: Both parents and staff widely accepted the intervention and found it beneficial. We identified four discussions that remained in the descriptive phase of the reflection process, four that reached the reflective phase, and one that reached the critical reflection phase. The descriptive discussions were characterized by using a single perspective to reflect, often based on personal opinions. The reflective discussions included analyzing interaction sequences from both staff and parent perspectives and were primarily based on actual observations of communication during medical rounds. The critical discussion led to a new awareness of current practices concerning parental involvement in decision-making. These discussions also utilized "what-if" thinking to evaluate potential new practices and their pros and cons. Conclusions: The intervention seems promising as it was perceived as beneficial by the recipients and facilitated reflection in most cases. However, to enhance the feasibility of the intervention, some improvements are discussed.